2014
DOI: 10.1016/j.seares.2013.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Benthic control freaks: Effects of the tubiculous amphipod Haploops nirae on the specific diversity and functional structure of benthic communities

Abstract: To cite this version:Carinne Rigolet, Stanislas F. Dubois, Éric Thiébaut. Benthic control freaks: Effects of the tubiculous amphipod Haploops nirae on the specific diversity and functional structure of benthic communities. Journal of Sea Research, Elsevier, 2014, 85, pp.413-427. 10.1016/j.seares.2013 01140607 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 102 publications
2
23
1
Order By: Relevance
“…The analysis of turnover in benthic assemblages revealed that the Haploops community shared very few species (ca. only 30%) with surrounding communities (Rigolet, Dubois & Thi ebaut 2014a). Stable isotope compositions of Haploops tubes and sediments revealed that the benthic primary production of the microphytobenthos (MPB) is enhanced in the Haploops community (Rigolet, Thi ebaut & Dubois 2014b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of turnover in benthic assemblages revealed that the Haploops community shared very few species (ca. only 30%) with surrounding communities (Rigolet, Dubois & Thi ebaut 2014a). Stable isotope compositions of Haploops tubes and sediments revealed that the benthic primary production of the microphytobenthos (MPB) is enhanced in the Haploops community (Rigolet, Thi ebaut & Dubois 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…The centre of the bay is composed of pure muds supporting a dense population of the tubiculous amphipod Haploops nirae (hereafter the Haploops community), forming a habitat with a dense tube mat (ca. 10 000 tubes m À2 ) and a unique species assemblage (Rigolet, Dubois & Thi ebaut 2014a).…”
Section: S a M P L I N G P R O T O C O Lmentioning
confidence: 99%
“…Epifaunal benthic invertebrates can be found in extremely high densities and generate biogenic structures that can influence the physical environment and provide important habitat for other species (Rigolet et al, 2014). The rugosity (complexity) and elevation of some of these structures is sufficient to reduce flow rates and resuspension and increase accretion (Wildish and Kristmanson, 1984).…”
Section: Ecosystem Function: Reef Building Water Velocity and Particmentioning
confidence: 99%
“…However, the functional diversity of marine protists could be studied using a biological trait approach, following the examples of research on terrestrial plants (Lavorel and Garnier, 2002), or benthic (Rigolet et al, 2014) and pelagic macroorganisms (Mouillot et al, 2014). Trait-based approaches are a field of functional ecology that consist in using functional traits to predict the performances of species within ecosystems (i.e.…”
Section: Introductionmentioning
confidence: 99%